Fishery and stock estimates of the silver pomfret, Pampus argenteus (Euphrasen), landed by gill netters at Veraval - Shubhadeep, Ghosh; Mohanraj, G; Asokan, P K; Dhokia, H K; Zala, M S; Bhint, H M (Indian Journal of Fisheries, 2016)
The fishery and population characteristics of silver pomfret Pampus argenteus (Euphrasen) caught by gillnetters off Veraval were studied for the period from 2003 to 2007. The average annual landing of P. argenteus was 114.5 t, which contributed 4.5% to the total gill net catches. The period from July to September was the most productive in terms of catch and catch rate. The length–weight relationship showed that the growth was isometric. The sex ratio was 1.75 in favour of females. Mature females occurred throughout the year, with maximum during June – November. The length at first maturity of female was 27.5 cm. The von Bertalanffy growth equation was: Lt = 41.57 [1 – e - 0.64 (t + 0.0315)]. The length at first capture (Lc) was 8.2 cm with recruitment taking place throughout the year with two peaks during February-March and in August. The natural mortality (M), fishing mortality (F) and total mortality (Z) were 1.20, 2.11 and 3.31 respectively. The exploitation ratio (E) was 0.64. The Maximum Sustainable Yield (MSY: 90 t) was lower than the average annual catch indicating over-exploitation of the species. The yield per recruit (Y/R) and biomass per recruit (B/R) was 38.31 g and 18.16 g respectively. An increase in relative yield by 17.18% would be obtained by decreasing the present level of fishing by 60%.